Determining the natural history of pancreatic cystic neoplasms: a Manitoban cohort study. Issue 4 (April 2016) - Broughton, Jon; Lipschitz, Jeremy; Cantor, Michael; Moffatt, Dana; Abdoh, Ahmed; McKay, Andrew
Abstract: Background: Most pancreatic cystic neoplasms (PCN) are thought to harbor a low malignant potential. This historical cohort study attempts to describe the natural history of these lesions in a provincial cohort, to assess the safety of non-surgical management. Pathological diagnosis of malignancy was the primary outcome measure of interest. Methods: All adult patients (age 18+) with PCN seen between 2000 and 2012 by the two main institutions in Manitoba were included in this study. PCN were graded as high and low risk, which dictated initial treatment plan (surgery or observation). Predictors of initial surgical treatment, delayed surgery in the observation group and the clinical/radiological predictors of malignancy were determined. Results: 497 patients were included in this study. 43 (8.7%) high-risk lesions underwent initial surgery, with 13 (30.2%) cases of malignancy discovered. 450 (90.5%) low-risk cysts were observed for a median of 17.3 months (range: 0.00–142.3). 29 (6.4%) cases of delayed surgery occurred, with malignancy discovered in five (17.2%). Conclusions: This study supports current selection criteria for management of PCNs. Due to the low incidence of malignancy in low-risk PCN, it appears that long-term observation is safe and should be the treatment modality of choice in the absence of high-risk features.